Penerapan Kaidah al-Ajru wa al- Ḍamān Lā Yajtama'ān pada Penyewaan Rumah di Desa Rumpia, Kecamatan Majauleng, Kabupaten Wajo, Sulawesi Selatan - Syandri Syandri; Santi Sarni; Sri Rahmayanti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to determine the application of the rules of al-Ajru wa al-Ḍamān Lā Yajtama'ān on house rentals in Rumpia Village, Majauleng District, Wajo Regency, South Sulawesi. The purpose of this study is an effort to obtain answers to muamalah problems, especially renting using a type of field research with fiqh, normative theological, and sociological approaches. The research results found are as follows; First, the house rental system in Rumpia village, Majauleng District, Wajo Regency is carried out by an oral contract between the tenant and the owner of the house without making a written contract with an annual payment system according to the agreement at the time of the contract. Second, the application of the rules of al-Ajru wa al-Ḍamāni Lā Yajtama'ān in the house rental system is still low. This is known from the system and policies implemented by the owner, most of which still require the tenant to pay compensation for damage to home facilities, whether caused by the negligence of the tenant or outside of the tenant's negligence. In fact, in the anafī school there is a rule (al-Ajru wa al-Ḍamān Lā Yajtama'ān) which explains the prohibition on collecting rental fees and replacement costs in one condition if the damage is not from the lessee. Based on this description, it can be understood that the application of the al-Ajru wa al-Ḍamān Lā Yajtama'ān rule in house rentals in Rumpia Village, Majauleng District, Wajo Regency is not yet fully actual.